May-Thurner Syndrome with Large Abdominal Varicosity, Treated Successfully Using Multiple Approaches. (30th April 2019) - Jia, Lori; Alexander, Jason; Skeik, Nedaa
Abstract : May-Thurner syndrome (MTS) is a venous outflow obstruction disorder characterized by compression of the left common iliac vein by an overriding right common iliac artery. MTS primarily affects young to middle-aged women, although many patients remain entirely asymptomatic. Anatomic variations of MTS, while uncommon, have been described. Treatment usually involves endovascular management, including thrombolysis and/or thrombectomy with or without inferior vena cava filter placement, followed by angioplasty and stenting of the left common iliac vein. We report a unique case of a 31-year-old woman who presented with MTS-related deep vein thrombosis accompanied by symptomatic abdominal and pelvic varicosities. The varicosities were treated successfully using multiple procedures, resulting in complete resolution of all symptoms. Our case discusses a treatment approach for an unusual presentation of MTS-related postthrombotic syndrome, and provides a brief literature review of MTS complications and management.